(untitled) (Annals of Medical Research, 2021)
Aim: The aim of our study was to evaluate the MCV, CRP, WBC changes in OA and to research whether or not any MCV, WBC changes pronto detectable by easy complete blood count (CBC), have diagnostic values for the prediction of progression of OA. Material and Methods: Eighty-two OA and sixty-nine control patients were registered in the study. The knee OA was classified by Kellgren-Lawrence (K&L) scale. Mean corpuscular volume (MCV), white blood cell (WBC) and C-reactive protein (CRP) levels were measured. Results: CRP and MCV levels were higher in OA than the control (p=.034 and p=.022 ). Multivariable regression analysis showed that increased age, BMI, and MCV levels are unassisted associated with increased risk of advance OA (OR=1.132, 95% CI:1.026- 1.249, p=.001; OR =1.148, 95% CI:1.062-1.242, p =.014 and OR = 0.492, 95% CI: 0.259-0.937, p =.031, respectively)Conclusion: We are suggesting that instead of any complex, costly methods, easy CBC and routine biochemical parameters at the initial presentation of OA patients could also be prognostic for the likely progression of OA.Keywords: Mean corpuscular volume; C-reactive protein; progression of knee osteoarthritis.